Dampak Ekonomi Kreatif Terhadap Peningkatan Pdb Dan Penyerapan Tenaga Kerja - Nidarmawati (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the contribution of the creative economy to Indonesia’s Gross Domestic Product (GDP) growth and employment absorption. Employing a quantitative approach with descriptive-inferential methods, the study utilizes secondary data from the Central Bureau of Statistics (BPS), the Ministry of Tourism and Creative Economy (Kemenparekraf), and other supporting publications. The findings reveal that the creative economy’s contribution to GDP increased significantly from approximately IDR 700 trillion in 2013 to IDR 1,532 trillion in 2024, representing a growth of about 119%. In terms of employment, this sector absorbed around 26.5 million workers in 2024, an increase of nearly 89% compared to 2013. Culinary, fashion, and craft subsectors emerged as the largest contributors. A simple regression analysis indicates a positive relationship between the contribution of the creative economy to GDP and the number of workers absorbed. Nevertheless, challenges remain, including limited access to financing, low digital literacy, and insufficient protection of intellectual property rights. These findings highlight the strategic role of the creative economy in national economic development, while also emphasizing the need for supportive policies, capacity building, and broader digital technology utilization to strengthen its sustainable contribution.